Corporate Governance Practices and Perceived Performance of Commercial Bank in Nepal - Rawat, Babu Ram (Journal of Research in Education, 2025)
This study explores the role of corporate governance in the performance of selected commercial banks in Nepal. The research aims to assess the current status of corporate governance practices, analyze the relationship between key governance elements and organizational performance, and examine the overall impact of corporate governance on perceived performance. A quantitative research including descriptive and casual comparative research design were adopted, with data gathered from 200 respondents using a self-administered survey questionnaire adapted from a previously validated instrument from employees working in both public and private banks, using convenience sampling. The study employed descriptive statistics, correlation, and multiple regression analyses to investigate the relationship between corporate governance practices and organizational performance. The findings indicate a positive correlation between effective corporate governance and improved perceived performance, highlighting the crucial role that transparency, accountability, fairness, discipline, and responsibility play in enhancing bank performance. The research underscores the importance of implementing corporate governance practices to maximize organizational efficiency. Additionally, the study suggests that fostering a supportive work environment can boost employee satisfaction and personal growth, contributing to the achievement of organizational goals and objectives.